Forum Kerukunan Umat Beragama In Aceh: Strategies, Roles and Barriers in Maintaining Interfaith Harmony - Nurdin AR; Siti Yusnaini; Anton Widyanto; Warul Walidin; Sulaiman Sulaiman (Ulumuna, 2021)
This research focuses on the roles and strategies that Forum Kerukunan Antar Umat Beragama/FKUB (interreligious harmony forum) plays in preserving interreligious harmony and analyzes the barries that it encounters. This study employed a qualitative approach, interviewing 79 informants consisting of the chair and members of FKUB in three districts and cities and the FKUB of Aceh province, as well as religious and community leaders. The research subjects were selected by purposive sampling method, and the data were analyzed using a descriptive approach. The research found that the interfaith harmony in the province of Aceh is well established. There are five strategies for realizing such harmony: tolerance, equality, cooperation, mutual respect, and communication. This study also revealed that the FKUB has carried out its role optimally in creating interfaith harmony in Aceh. However, it experiences some obstacles due to sociological, internal, and external factors. Despite these challenges, the FKUB in Aceh has relatively been able to overcome those obstacles.